Analysis and comparison of two different ultra-precision manufacturing methods for off-axis parabolic mirror with single point diamond turning. (November 2016) - Ji, Shijun; Yu, Huijuan; Zhao, Ji; Liu, Xiaolong; Hu, Ming
Off-axis aspheric mirror is an important component widely used in optical system and precision measurement instrument. Off-axis parabolic surface is one typical shape of off-axis aspheric mirrors which can enlarge focal length and widen field-of-view. Two typical ultra-precision turning methods which are turning the cylindrical blank by revolving around the axis of parabolic surface (TPS) and revolving around the axis of cylindrical surface (TCS) are analyzed and compared for off-axis parabolic surface in this article. Three-axis (X, Z, C) turning machine is applied and kinematic analyses of two linear axes (X, Z) are studied during cutting with the single point diamond turning. The tool paths are generated and installation errors are analyzed under two different conditions. Primary experiments are conducted to verify the effectiveness of theoretical analyses. The obtained results demonstrate that the surface machined with TPS method has better machining quality than the one machined with TCS method.